Teleconsultation in Hospital Service: Implementation Challenge - Ernawati, Cicilia Maria; Agustina, Else; Suryanto, Suryanto (Fakultas Kedokteran Universitas Brawijaya, 2022)
Teleconsultation is one of the telemedicine services provided by hospitals and is getting popular during the Covid-19 pandemic. As a new service model, developing a quality management system that can ensure the effectiveness and safety of this service to provide users' satisfaction is necessary. This research aimed to identify and analyze the process and problems of teleconsultation services. This research was qualitative with a descriptive case study approach to get a detailed picture of the teleconsultation process in a hospital and its issues. The study was conducted from September to October 2021 in a type C private hospital in Malang. Data were obtained from interviews with officers and patient feedback on teleconsultation services. Problems in teleconsultation services in the hospital were ineffective communication, limited-service coverage, lack of support for medical support facilities, technological constraints, lack of understanding of service flow, and cost affordability.